PENGARUH ATMOSFER PUSAT BELANJA PADA SHOPPING VALUE - Astrid Kusumowidagdo; Agus Sachari; Pribadi Widodo (Jurnal Siasat Bisnis, 2013)
AbstractAt the moment, the creation of shopping environment design that provides certain sensation and experience become strategy of the shopping center. This research aims to find out about the influence of shopping center’s atmosphere towards shopping value. The formative factors of shopping centre’s atmosphere are architectural features, interior features and support facilities. The research begins with a focus group to adjust the indicators of the previous research to the present research’s object. The next stage of research is done with a multiple regression analysis. The research object is the atmosphere condition of Senayan City shopping center in Jakarta and the subjects are samples totaling to sixty people. The samples are visitors from the middle-class segment between the age of 18-35.The research finds that architectural features, interior features and support facilities collectively bring an influence towards shopping value in Senayan City Pusat belanja, wether partially, only interior features show the significant influence towards shopping value.Keywords: design, atmosphere, shopping centre, shopping value.AbstrakSaat ini penciptaan lingkungan belanja dengan yang memberikan sensasi dan pengalaman telah menjadi bagian dari strategi bisnis pusat belanja. Penelitian ini bertujuan untuk menelusuri pengaruh atmosfer pusat belanja terhadap shopping value. Atmosfer pusat belanja dibentuk oleh faktor-faktor yaitu fitur arsitektur, fitur interior dan fasilitas penunjang. Penelitian ini diawali dengan focus group untuk penentuan indikator yang tepat dan dilanjutkan dengan survey pada 60 orang dengan usia 18-35 tahun yang bersegmen menengah. Obyek penelitian adalahatmosfer dari pusat belanja Senayan City. Hasil penelitian menunjukkan terdapat hubungan dari faktor-faktor atmosfer pusat belanja secara serempak pada shopping value, sedangkan secara parsial hanya fitur interior yang memberikan pengaruh signifikan pada shopping value.Kata Kunci: desain, atmosfer, pusat belanja, shopping value.